Sphingosine 1‐phosphate has anti‐apoptotic effect on liver sinusoidal endothelial cells and proliferative effect on hepatocytes in a paracrine manner in human. Issue 11 (28th November 2014) - Nowatari, Takeshi; Murata, Soichiro; Nakayama, Ken; Sano, Naoki; Maruyama, Takehito; Nozaki, Reiji; Ikeda, Naoya; Fukunaga, Kiyoshi; Ohkohchi, Nobuhiro
Abstract : Aim: Sphingosine 1‐phosphate (S1P) is a bioactive sphingolipid metabolite released from erythrocytes and platelets, and is a potent stimulus for endothelial cell proliferation. However, the role of S1P on human liver sinusoidal endothelial cells (LSEC) remains unclear. The proliferation and inhibition of apoptosis in LSEC are involved in the promotion of liver regeneration and the suppression of liver injury after liver resection and transplantation. The aim of this study is to investigate the role of S1P on human LSEC and the interaction between S1P and LSEC in hepatocyte proliferation in vitro . Methods: Immortalized human LSEC were used. LSEC were cultured with S1P, and the cell proliferation, anti‐apoptosis, signal transductions and production of cytokines and growth factors were subsequently examined. To investigate the interaction between S1P and LSEC in hepatocyte proliferation, primary human hepatocytes were cultured with the supernatants of LSEC with and without S1P. DNA synthesis and signal transductions in hepatocytes were examined. Results: S1P induced LSEC proliferation through activation of Akt and extracellular signal‐related kinase pathways and suppressed LSEC apoptosis by affecting the expression levels of Bcl‐2, Bax and cleaved caspase‐3. S1P promoted interleukin‐6 (IL‐6) and vascular endothelial growth factor (VEGF) production in LSEC. The supernatants of LSEC cultured with S1P enhanced hepatocyte DNA synthesis more strongly than the supernatants of LSEC cultured without S1P through activation of the signal transducer and activator of transcription‐3 pathway. Conclusion: S1P has proliferative and anti‐apoptotic effects and promotes the production of IL‐6 and VEGF in human LSEC, thereby promoting hepatocyte proliferation.